MiR-487a-3p upregulated in type 1 diabetes targets CTLA4 and FOXO3. (August 2018) - Zurawek, Magdalena; Dzikiewicz-Krawczyk, Agnieszka; Izykowska, Katarzyna; Ziolkowska-Suchanek, Iwona; Skowronska, Bogda; Czainska, Maria; Podralska, Marta; Fichna, Piotr; Przybylski, Grzegorz; Fichna, Marta; Nowak, Jerzy
Abstract: Aims: Type 1 diabetes (T1D) is an autoimmune disorder caused by the T-cell mediated destruction of the insulin-producing pancreatic beta cells. T1D is a consequence of complex processes, influenced by genetic, epigenetic and environmental factors. MicroRNAs (miRNAs) are small non-coding RNAs that target multiple mRNAs and regulate gene expression. The implication of miRNAs in T1D pathogenesis, as potential modulators of immune response genes, remains poorly defined. The aim of this study was to investigate the expression profile of miRNAs in new onset T1D and the impact of deregulated miRNAs on target genes. Methods: Total RNA from peripheral blood mononuclear cells of newly diagnosed T1D pediatric patients and age-matched controls was screened for disease-associated miRNAs by a microarray analysis, with subsequent validation by quantitative reverse-transcription polymerase chain reaction (qRT-PCR). miRNA targets were identified by luciferase reporter assays. Results: The microarray analysis revealed 91 deregulated miRNAs ( P  < 0.05) in T1D group compared to non-diabetic controls. Within this group we observed one upregulated and seven downregulated miRNAs with fold change >2.0. qRT-PCR validation revealed overexpression of miR-487a-3p which has not been previously reported in the context of T1D. Luciferase reporter assays indicated CTLA4 and FOXO3 genes as miR-487a-3p targets. Conclusion: Our study suggests that miR-487a-3p might repress CTLA4 and FOXO3 by binding to their 3'UTRs and contribute to the development of T1D.